Kekuatan Hukum Sertifikat Hak Milik Berdasarkan Alas Hak Cacat dalam Perspektif Asas Nemo Plus Juris: Studi Kasus Putusan PN Tondano Nomor 97/Pdt.G/2024/PN Tnn - Reynold Simandjuntak; Jeshica Sampe Toding; Winda Winda (Pusat Riset dan Inovasi Nasional, 2025)
The authoritative document entity commonly referred to as the Certificate of Ownership (SHM) is legally constructed as a supremacy manifestation of the dominant right to geocadastral space, as determined by the legislative norm of lex generalis contained in Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA). Terminologically, Article 20 paragraph (1) of the UUPA affirms that the dominant right is an absolute hereditary prerogative and has the highest legal density in the agrarian civil structure. This study is intended as an academic examination of the legal empire of the SHM document which was born from a legal substratum that experienced validity dysfunction, using the doctrinal paradigm of the principle of Nemo Plus Juris ad alium transferre potest quam ipse habet. This research is articulated through a doctrinal-normative legal approach based on the explication of positive legal literature and judicial jurisprudence. The results of the investigation conclude that the SHM entity derived from the legal anomaly-affected legal basis does not have normative validity that can be constitutionally maintained. The internality of the Nemo Plus Juris principle shows that legal actors do not have the authority to transfer rights that are not legally attached to them, so that the legal alienation process by the defendants in the form of a sale and purchase is null and void in material law. The implication is that the plaintiff's legal standing as a legal subject with land rights that are previously legally valid has the legitimacy to file an administrative cancellation of the SHM and reconstruction of the ownership status to the entity that is legally entitled. The judicium issued by the Panel of Judges at the Tondano District Court in the a quo case has substantially been in line with the principles of proportionality and legality, and has utilized legal instruments as a protective medium for the existence of legitimate agrarian rights. This confirms the supremacy of law in maintaining the integrity of the national land system from manipulative penetration based on flawed formalities of the right base.